Študij geografije v Mariboru - Kolnik, Karmen (Revija za geografijo, 2006)
The article presents the analysis of the quantitative and qualitative development of geography studies in Maribor. We have analysed the educational achievements and achievements in researches of students and professors from the first beginnings in the middle of the previous century untill today. The determined progress is noticeable in the growing number and variety of educational programmes ( from higher educational degree to university) as well as it is noticeable from the growing number of its performers, research programmes, skilled educational teams and of course, from the wide response of the achieved results itself.
Keywords: geografija; geography; Maribor; podiplomski študij; študijski programi; visokošolski študij